Perbandingan rencana strategis 3 bank (Bank Bukopin, Bank Panin, dan Bank ICBC) tahun 2021 berdasarkan tujuan perusahaan menurut Glueck - Zaharani, Chanina Mumtaza; Putri, Dinsa Selia; Setyowati, Diyah Ajeng (Maliki Interdisciplinary Journal, 2023)
Strategic planning is one of the many developing planning concepts, in which planning is one of the management functions. Every expert in stating management functions does not fail to include planning as one of the functions and this function is always placed first. This research focuses on banking industry companies, namely PT Bank Panin Financial Tbk, PT Bank KB Bukopin Tbk, and PT. ICBC Tbk. The aim of this research is to find out the strategic plans contained in the three banks. The research method used is the literature review method.